2019
DOI: 10.4103/ijem.ijem_559_18
|View full text |Cite
|
Sign up to set email alerts
|

Visceral adiposity index: Simple Tool for assessing cardiometabolic risk in women with polycystic ovary syndrome

Abstract: Aim: To study visceral adiposity index (VAI) and its association with cardiometabolic risk in different phenotypes of polycystic ovary syndrome (PCOS). Materials and Methods: It is a case–control cross-sectional study where 100 reproductive age (18–35 years) women with PCOS were classified in different phenotypes as per Rotterdam criteria and compared with age and Body mass index (BMI) matched 50 eumenorrheic and nonhirsute women. Various anthropometric, clinical, bioch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…Review of the literature reveals several studies investigating the relationship of VAI and LAP with cardiometabolic risk factors in women with PCOS. Agrawal et al [28] examined the possible relationship between VAI and cardiometabolic risk factors in patients with PCOS phenotypes classified according to the Rotterdam criteria and in healthy controls. They showed higher mean VAI values in the PCOS group.…”
Section: Discussionmentioning
confidence: 99%
“…Review of the literature reveals several studies investigating the relationship of VAI and LAP with cardiometabolic risk factors in women with PCOS. Agrawal et al [28] examined the possible relationship between VAI and cardiometabolic risk factors in patients with PCOS phenotypes classified according to the Rotterdam criteria and in healthy controls. They showed higher mean VAI values in the PCOS group.…”
Section: Discussionmentioning
confidence: 99%
“…North India stated phenotype C to be most common [42][43][44]. In contrast, other groups again from North India [45][46][47] as well as East India [48,49] have detailed increased frequency of phenotype A in their populations.…”
Section: Plos Onementioning
confidence: 99%
“…Another important finding of our study was LAP and VAI were comparable amongst PCOS phenotypes in the total and lean groups, but in the obese group phenotype A showed markedly higher LAP and VAI compared to phenotypes D and C respectively. In addition, recent studies from India have shown that the classic hyperandrogenic phenotypes of PCOS present with elevated VAI [42,61]. Lack of more significant differences in metabolic traits across PCOS phenotypes in obese group suggests that obesity may mask differences in intrinsic harmful metabolic profiles.…”
Section: Plos Onementioning
confidence: 99%
“…As a quantitative and easy-to-use clinical surrogate of VAT, VAI has been the focus of many previous studies using it as a promising tool for screening MetS [ 15 , 17 ] and identifying high-risk patients [ 18 ]. However, previous studies have reported variable screening accuracies of VAI for MetS, and it is unclear whether it is justifiable to use VAI as a screening tool for MetS.…”
Section: Introductionmentioning
confidence: 99%